Patient-Determined Important Change for the Neck Disability Index With Application of Credibility Analysis: An Exploratory Study. - Young, Brian A.; Boland, David M.; Koppenhaver, Shane L.; Puentedura, Emilio J.; Cleland, Joshua A. (Journal of Manipulative & Physiological Therapeutics, 2024)
The purposes of this study were to preliminarily report patient-identified change for the neck disability index (NDI) as either important or not important with time between follow-up of approximately 7 to 10 days and assess the credibility of the preliminary results with the use of a recently established credibility instrument. This study was a secondary analysis from a primary randomized clinical trial assessing short-term physical therapist care for individuals with mechanical neck pain. Neck disability index scores and participant-reported importance of global rating of change scores from 42 participants were analyzed from a randomized clinical trial assessing short-term responses to thoracic manipulation and dry needling for neck pain. Patient-important change was computed using receiver operating characteristic curves, and statistical error of the measurement was calculated using (SD × [1 − r]1/2) × 1.96 to assess measurement error at the 95% CI. Thirty-six participants rated global rating of change as important, and 6 rated it as not important. Patient-important change was calculated at 3.5 NDI points on a 0 to 50 NDI scoring scale. This value exceeded the statistical error, which was calculated at 2.16 NDI points. The credibility analysis revealed that 4 of 5 criteria showed strong credibility for the patient-important change estimate. Using patient-determined importance to dichotomize improvement may yield a lower threshold than current researcher-defined methods. Clinically, these results may be more responsive to patient-centric change than using previously reported minimal clinically important difference data.